An injectable antioxidant type silicon-calcium-based bioactive dental paste, preparation method and application

CN122997966APending Publication Date: 2026-10-30CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610999570.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,传统的MTA仍然存在操作性能不佳、无法注射,固化速度较慢,遇到含水液相容易溃散游离等问题

Benefits of technology

1、本发明采用包含甲基丙烯酰化明胶(Gelma)和氧化结冷胶(OGG)的水溶液作为液相。在糊剂调制及应用过程中,Gelma提供了基础的光交联能力,同时氧化结冷胶分子中的醛基与Gelma中的氨基发生席夫碱化学反应;此外,硅酸钙水化过程中释放的Ca2+能够与氧化结冷胶表面的羧基发生静电结合,从而构建出光交联-席夫碱交联-离子交联协同的多重固化网络;该特定的液相体系使得糊剂保持了良好的流变学特性,注射率维持在较高水平(90%以上),操作顺畅且不易堵塞;多重交联网络的快速构建,在光照条件下不仅使糊剂在液相环境中具备良好的初期抗水下溃散能力,还能将固化时间控制在较短范围内(约9~12秒),有效解决了传统改性手段中抗溃散与快速固化相互制约的技术痛点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122997966A_ABST
    Figure CN122997966A_ABST
Patent Text Reader

Abstract

The application discloses an injectable antioxidant type silicon-calcium-based bioactive dental paste, a preparation method and application, and belongs to the technical field of biomedical materials. The paste is prepared from a solid-phase powder and a liquid phase. The solid-phase powder is a magnesium-cerium co-doped dicalcium silicate powder, and the liquid phase comprises a water solution of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, methacrylated gelatin and oxidized gelling gum. The application induces lattice oxygen vacancies through magnesium-cerium double metal ion co-doping, endows the material with excellent endogenous active oxygen scavenging capacity, and effectively relieves local oxidative stress damage. Meanwhile, the paste is combined with multiple networks such as photo-crosslinking and Schiff base chemical crosslinking of the liquid phase, realizes rapid controllable solidification under the premise of maintaining a high injection rate, and has extremely strong underwater anti-collapse performance. The material has excellent bioactivity and early bone mineralization induction capacity, and is suitable for dental filling and repairing fields such as root canal filling, apex induction shaping and pulp capping.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical materials technology, specifically relating to an injectable antioxidant silicon-calcium-based bioactive dental paste, its preparation method, and its application. Background Technology

[0002] Pulpitis is an inflammatory lesion of the dental pulp tissue caused by factors such as microbial infection and trauma. As a common oral disease, it can lead to severe pain, pulp necrosis, and irreversible damage to the tooth structure. The dental pulp is mainly composed of blood vessels, nerves, and connective tissue, and is essential for root development and apical closure, playing a crucial role in maintaining normal tooth function and long-term preservation. Therefore, vital pulp preservation therapy (VPT), ​​as a treatment method aimed at protecting pulp vitality, has received increasing attention. As a dental filling and restorative material, the biological properties of pulp capping agents have a significant impact on the treatment outcome of pulpitis. Currently, there are many types of dental filling materials used clinically, including zinc oxide eugenol cement, glass ionomer cement, and bioceramic self-curing materials, but no single material can simultaneously meet all performance requirements.

[0003] Mineral trioxide aggregates (MTA) are high-performance bioceramic materials with good biocompatibility, bioactivity, apatite mineralization ability, and sealing properties, thus successfully used in root canal treatment, pulpotomy, revascularization, pulp capping, and retrograde filling for periapical diseases. However, traditional MTA still suffers from poor maneuverability, inability to be injected, slow curing speed, and easy disintegration and freeing when exposed to aqueous liquids. To address the poor injectability and anti-disintegration properties of calcium silicate-based self-curing materials, researchers have proposed various strategies, primarily by adding organic polymers such as sodium alginate, chitosan, and cellulose to improve the rheological properties of the paste, thereby giving it good injectability and maneuverability. However, this further prolongs the curing time of the paste. For example, patent application CN106693063B discloses an anti-disintegration calcium silicate-based composite bone cement and its preparation method, which improves the injectability and anti-disintegration properties of the calcium silicate-based bone cement by introducing sodium alginate, but significantly prolongs the final setting time of the bone cement.

[0004] Furthermore, conventional MTA can induce elevated levels of reactive oxygen species (ROS) in dental pulp stem cells (DPSCs), potentially leading to cell death, reduced osteogenic / odontogenic differentiation potential, and further exacerbating inflammation. Patent application CN118370689A discloses a strontium-doped root canal filling paste and its preparation method, which to some extent improves upon existing materials' problems of long curing time, low strength, poor mineralization, and insufficient adhesion to the root canal wall. However, the material disclosed in this patent is difficult to remove ROS. In addition, its hydration products significantly increase the pH of surrounding tissues, creating an alkaline microenvironment, which can further activate inflammation-related signaling pathways and promote the release of inflammatory factors, thereby synergistically exacerbating tissue inflammatory damage in conjunction with oxidative stress.

[0005] Therefore, there is an urgent need to develop an injectable, anti-collapse, and antioxidant silicon-calcium-based bioactive dental paste material. Summary of the Invention

[0006] In view of the shortcomings of the prior art, the purpose of this invention is to provide an injectable antioxidant silicon-calcium based bioactive dental paste, its preparation method and application, thereby solving the problems in the prior art.

[0007] The objective of this invention can be achieved through the following technical solutions: An injectable antioxidant silicon-calcium-based bioactive dental paste, formulated from solid powder and liquid phase; The solid powder includes: magnesium-cerium co-doped dicalcium silicate powder; The liquid phase comprises an aqueous solution of lithium phenyl (2,4,6-trimethylbenzoyl)phosphate, methacrylamide gelatin, and oxidized gellan gum.

[0008] Furthermore, in the dental paste, the mass percentage of the solid powder is 10% to 30%.

[0009] Furthermore, in the magnesium-cerium co-doped dicalcium silicate powder, based on the total molar amount of the three metal elements calcium, magnesium, and cerium, the molar percentage of magnesium is 2.5% to 10%, and the molar percentage of cerium is 2.5% to 7.5%. Furthermore, the total molar amount of the three metallic elements calcium, magnesium, and cerium is in a molar ratio of 2:1 to that of silicon.

[0010] Furthermore, in the liquid phase, the mass-volume concentration of methacrylamide gelatin is 5 g / 100 mL to 15 g / 100 mL, and the mass-volume concentration of oxidized gellan gum is 1 g / 100 mL to 5 g / 100 mL.

[0011] Furthermore, the mass-volume concentration of lithium phenyl (2,4,6-trimethylbenzoyl)phosphate in the liquid phase is 0.5 g / 100 mL.

[0012] The preparation method of the above-mentioned injectable antioxidant silica-calcium-based bioactive dental paste includes the following steps: Magnesium-cerium co-doped dicalcium silicate powder was prepared by sol-gel method and used as a solid-phase powder. Under light-protected conditions, methacrylamide gelatin, oxidized gellan gum, and lithium phenyl (2,4,6-trimethylbenzoyl)phosphate were dissolved in water to obtain a liquid phase. The solid powder and the liquid phase are uniformly mixed to obtain an injectable antioxidant silicon-calcium-based bioactive dental paste.

[0013] Furthermore, the magnesium-cerium co-doped dicalcium silicate powder is prepared by the sol-gel method, specifically including the following steps: The silicon source was added to ethanol and mixed and stirred. Then deionized water was added to obtain solution a. The pH value of solution a was adjusted to 1-2 with nitric acid and stirred until the silicon source was completely hydrolyzed to obtain solution b. Calcium source, magnesium source and cerium source are added to solution b, and the mixture is stirred continuously to obtain solution c. Solution c is cured until gelation occurs and then dried to obtain dry gel. The dry gel was ground into a fine powder, then calcined and cooled to room temperature, and then ground again to obtain the magnesium-cerium co-doped dicalcium silicate powder.

[0014] Furthermore, the preparation process of the methacrylamide gelatin includes: Add gelatin to phosphate buffer and stir until completely dissolved to form solution d; Methacrylic anhydride was added to solution a and reacted under light-protected conditions; then it was diluted with phosphate buffer solution and the reaction was stirred.

[0015] Finally, dialysis and freeze-drying were performed to obtain methacrylated gelatin.

[0016] Furthermore, the preparation process of the oxidized gellan gum includes: Gellan gum is dissolved in deionized water to form solution e; Sodium periodate was added to solution e and stirred for 4 hours in the dark; then ethylene glycol was added and stirred. Finally, after dialysis and freeze-drying, oxidized gellan gum was obtained.

[0017] The above-mentioned injectable antioxidant silicon-calcium-based bioactive dental paste is used in the preparation of dental filling and restorative materials, which are used for root canal filling, apexification, or pulp capping.

[0018] The beneficial effects of this invention are: 1. This invention uses an aqueous solution containing methacrylamide gelatin (Gelma) and oxidized gellan gum (OGG) as the liquid phase. During paste preparation and application, Gelma provides basic photocrosslinking capability, while the aldehyde groups in the oxidized gellan gum molecules undergo a Schiff base chemical reaction with the amino groups in Gelma; furthermore, the Ca released during the hydration of calcium silicate... 2+ It can electrostatically bind with the carboxyl groups on the surface of oxidized gellan gum, thereby constructing a multi-curing network with synergistic photocrosslinking, Schiff base crosslinking, and ionic crosslinking. This specific liquid-phase system enables the paste to maintain good rheological properties, keep the injection rate at a high level (above 90%), and ensure smooth operation without clogging. The rapid construction of the multi-crosslinking network not only enables the paste to have good initial resistance to underwater collapse in the liquid-phase environment under light conditions, but also controls the curing time to a short range (about 9~12 seconds), effectively solving the technical pain point of mutual constraint between anti-collapse and rapid curing in traditional modification methods.

[0019] 2. The solid-phase powder of this invention incorporates magnesium and cerium co-doped dicalcium silicate material; wherein, the cerium ions are based on Ce. 3+ / Ce 4+ The reversible valence cycle mechanism can mimic the activities of superoxide dismutase (SOD) and catalase; magnesium ions help stabilize the free radical structure and protect mitochondria; the co-doping of both induces lattice oxygen vacancies inside dicalcium silicate, enhancing the electron transfer efficiency within the system; based on the above-mentioned lattice-level ion catalysis mechanism, the paste has the ability to continuously disproportionate superoxide anions and decompose hydrogen peroxide, achieving spontaneous reactive oxygen species scavenging; it can effectively reduce oxidative stress damage caused by material implantation or changes in the local microenvironment, thereby reducing the risk of secondary inflammatory reactions in surrounding tissues.

[0020] 3. This invention uses dicalcium silicate as an inorganic framework and quantitatively introduces magnesium and cerium ions into the material lattice from bottom to top through a specific sol-gel process to form a stable multi-element inorganic solid phase. The magnesium and cerium dual-ion co-doping structure exhibits superior biophysical activity compared to single metal doping. This material can promote the deposition of dense apatite crystals on the paste surface. In in vitro cell evaluation, this component can enhance cell viability, increase the expression activity of alkaline phosphatase (ALP), and promote the formation of mineralized nodules in the extracellular matrix, showing good potential for early osteogenic and odontogenic induction. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 These are static anti-collapse test images of the pastes prepared in Examples 1-5 and Comparative Examples 1-3 of the present invention without ultraviolet light irradiation; Figure 2 These are static anti-collapse test images of the pastes prepared in Examples 1-5 and Comparative Examples 1-3 of this invention under ultraviolet light irradiation. Figure 3 The photocuring time diagrams are for the pastes prepared in Examples 1-5 and Comparative Examples 2-3 of this invention. Figure 4 The injection rate test graphs are for the pastes prepared in Examples 1-5 and Comparative Examples 2-3 of this invention. Figure 5 This is a diagram illustrating the injection process of the paste prepared in Examples 2-5 of the present invention; Figure 6 The graph shows the overall antioxidant performance of the pastes prepared in Example 1 and Comparative Examples 2-3 of this invention. Figure 7 The above figures show the H2O2 removal results of the pastes prepared in Example 1 and Comparative Examples 2-3 of this invention. Figure 8 The images show SEM images of the apatite deposition on the surface of the pastes prepared in Example 1 and Comparative Example 2 of this invention. Figure 9 Cell activity diagrams of the pastes prepared in Example 1 and Comparative Examples 2-3 of this invention; Figure 10 Alkaline phosphatase (ALP) staining images of the pastes prepared in Example 1 and Comparative Examples 2-3 of this invention; Figure 11 Alizarin Red (ARS) staining images of the pastes prepared in Example 1 and Comparative Examples 2-3 of this invention. Detailed Implementation

[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] In the examples and comparative examples, the sources of the relevant raw materials are as follows: Lithium phenyl (2,4,6-trimethylbenzoyl)phosphate: photoinitiator LAP, CAS: 85073-19-4, purity ≥99.5%, Shanghai Yinchang New Materials Co., Ltd.

[0025] Gelatin, reagent grade, catalog number G274269, CAS: 9000-70-8, Shanghai Aladdin Biochemical Technology Co., Ltd.

[0026] Gellan gum, biotechnology grade, product number G821481, CAS: 71010-52-1, Shanghai Maclean Biochemical Technology Co., Ltd.

[0027] Primary dental pulp stem cells (SHED): Dental pulp stem cells are isolated from the pulp of deciduous teeth shed by children.

[0028] Example 1 An injectable antioxidant calcium silicate-based bioactive dental paste is prepared from a solid powder and a liquid phase; the solid powder is magnesium-cerium doped dicalcium silicate powder; the liquid phase contains at least an aqueous solution of methacrylamide gelatin (Gelma) and oxidized gellan gum.

[0029] This invention utilizes the photocrosslinking properties of methacrylamide gelatin to impart rapid curing ability to the paste; the aldehyde groups in oxidized gellan gum can undergo a Schiff base reaction with the amino groups in gelma molecules, achieving chemical crosslinking between the two. Simultaneously, the Ca released continuously during the hydration of calcium silicate... 2+ Through electrostatic attraction, it interacts with the carboxylic acid groups (-COO) on the surface of OGG. - Ion adsorption occurs, forming complementary charge bonds. This Ca... 2+ Mediated ionic crosslinking further strengthens the hydrogel network, significantly improving the overall mechanical properties of the material.

[0030] Magnesium and cerium ions can synergistically scavenge ROS, with cerium ions relying on Ce. 3+ / Ce 4+ The reversible valence cycle mimics the activity of SOD and CAT, directly disproportionating superoxide anions, decomposing hydrogen peroxide, and quenching hydroxyl radicals. Magnesium ions stabilize free radical structures, activate in vivo antioxidant enzymes, and protect mitochondria, reducing ROS generation. Doping with dicalcium silicate introduces lattice oxygen vacancies, synergistically enhancing electron transfer and efficiently blocking oxidative stress damage. Therefore, magnesium and cerium ions endow this material with excellent antioxidant capabilities.

[0031] The preparation method of the injectable antioxidant silicon-calcium-based bioactive dental paste of the present invention specifically includes the following steps: S1, magnesium-cerium-doped dicalcium silicate powder was prepared by sol-gel method to obtain solid phase powder; Specifically, the preparation process of solid-phase powder (magnesium-cerium-doped dicalcium silicate powder) includes: S1-1, 0.1 mol of silicon source (SiO2) is added to 1 mol of ethanol and mixed and stirred. Then 0.5 mol of deionized water is added to obtain mixed solution a. The pH of mixed solution a is adjusted to between 1 and 2 with nitric acid. The mixture is stirred at 60°C until the silicon source is hydrolyzed to obtain mixed solution b. S1-2, a total of 0.2 mol of calcium source (CaO), magnesium source (MgO) and cerium source (CeO) were added to the above mixed solution b, wherein the amount of magnesium ions introduced was 5% mol and the amount of cerium ions introduced was 5% mol. The mixture was stirred continuously to obtain a clear mixed solution c, which was cured at 60℃ for 1 day until gelation occurred, and then dried thoroughly in a drying oven at 120℃ to obtain a dry gel. S1-3, the dry gel is ground into fine powder, then calcined at 800°C for 3 hours, rapidly cooled to room temperature, and finally the sintered clinker is ground to obtain magnesium-cerium-doped dicalcium silicate powder.

[0032] S2, 0.5% (w / v) phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 10% (w / v) methacrylamide gelatin and 2.5% (w / v) oxidized gellan gum are added to water under light-protected conditions and dissolved completely to obtain a homogeneous liquid phase. The preparation process of methacrylamide gelatin (Gelma) includes: S2-1, Add 10% (w / v) gelatin to phosphate buffer and stir until completely dissolved to form solution d; S2-2, 8% methacrylic anhydride was slowly added to solution d and reacted for 3 hours in the dark; then it was diluted 5 times with phosphate buffer solution and stirred for 15 minutes, wherein the volume of methacrylic anhydride added accounted for 8% of the phosphate buffer solution.

[0033] S2-3, after dialyzing the mixed solution for 7 days, followed by freeze-drying, yielded Gelma.

[0034] The preparation process of oxidized gellan gum includes: S2-4, add 2% (w / v) gellan gum to deionized water to dissolve, forming solution e; S2-5, add 0.4% (w / v) sodium periodate to solution e and stir for 4 hours in the dark; then add 2.5% ethylene glycol and stir for 1 hour to terminate the reaction, wherein the volume of ethylene glycol added is 2.5% of the volume of deionized water added; S2-6, the mixed solution was dialyzed for 3 days and then freeze-dried to obtain oxidized gellan gum.

[0035] S3, 20wt% solid powder and liquid phase are uniformly mixed in proportion to obtain the injectable photocrosslinkable silicon-calcium based material (dental paste).

[0036] Example 2 (1) Magnesium-cerium-doped dicalcium silicate powder was prepared by sol-gel method to obtain solid powder. The amount of magnesium ions was 5% mol and the amount of cerium ions was 7.5% mol. The molar ratio of CaO+CeO+MgO:SiO2 was 2:1. The synthesis steps of magnesium-cerium-doped dicalcium silicate powder were the same as those in Example 1, except that the amount of cerium ions introduced was changed.

[0037] (2) 0.5% (w / v) of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 10% (w / v) methacrylamide gelatin and 2.5% (w / v) oxidized gellan gum were added to water under light-protected conditions and dissolved completely to obtain a homogeneous liquid phase. The synthesis methods of gelma and oxidized gellan gum were the same as in Example 1.

[0038] (3) Mix 20wt% of solid powder with liquid phase to obtain injectable antioxidant silicon-calcium based material.

[0039] Example 3 (1) Magnesium-cerium doped dicalcium silicate powder was prepared by sol-gel method to obtain solid powder. The amount of magnesium ions was 5% mol and the amount of cerium ions was 2.5% mol. The molar ratio of CaO+CeO+MgO:SiO2 was 2:1. The synthesis steps of magnesium-cerium doped dicalcium silicate powder were the same as those in Example 1, except that the amount of cerium ions introduced was changed.

[0040] (2) 0.5% (w / v) of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 10% (w / v) methacrylamide gelatin and 2.5% (w / v) oxidized gellan gum were added to water under light-protected conditions and dissolved completely to obtain a homogeneous liquid phase. The synthesis methods of gelma and oxidized gellan gum were the same as in Example 1.

[0041] (3) Mix 20wt% of solid powder with liquid phase to obtain injectable antioxidant silicon-calcium based material.

[0042] Example 4 (1) Magnesium-cerium doped dicalcium silicate powder was prepared by sol-gel method to obtain solid powder. The amount of magnesium ions was 10% mol and the amount of cerium ions was 2.5% mol. The molar ratio of CaO+CeO+MgO:SiO2 was 2:1. The synthesis steps of magnesium-cerium doped dicalcium silicate powder were the same as those in Example 1, except that the amount of magnesium and cerium ions introduced was changed.

[0043] (2) 0.5% (w / v) of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 15% (w / v) methacrylamide gelatin and 1% (w / v) oxidized gellan gum were added to water under light-protected conditions and dissolved completely to obtain a homogeneous liquid phase. The synthesis methods of gelma and oxidized gellan gum were the same as in Example 1.

[0044] (3) Mix 30wt% of solid powder with liquid phase to obtain injectable antioxidant silicon-calcium based material.

[0045] Example 5 (1) Magnesium-cerium doped dicalcium silicate powder was prepared by sol-gel method to obtain solid powder. The amount of magnesium ions was 2.5% mol and the amount of cerium ions was 7.5% mol. The molar ratio of CaO+CeO+MgO:SiO2 was 2:1. The synthesis steps of magnesium-cerium doped dicalcium silicate powder were the same as those in Example 1, except that the amount of magnesium and cerium ions introduced was changed.

[0046] (2) 0.5% (w / v) of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 5% (w / v) methacrylamide gelatin and 5% (w / v) oxidized gellan gum were added to water under light-protected conditions and dissolved completely to obtain a homogeneous liquid phase. The synthesis methods of gelma and oxidized gellan gum were the same as in Example 1.

[0047] (3) Mix 10wt% of solid powder with liquid phase to obtain injectable antioxidant silicon-calcium based material.

[0048] Comparative Example 1 (1) Dicalcium silicate powder was prepared by sol-gel method to obtain solid powder. The molar ratio of CaO:SiO2 was 2:1. The synthesis steps were the same as in Example 1.

[0049] (2) Mix 20wt% of solid powder with deionized water to obtain injectable antioxidant silicon-calcium based material.

[0050] Comparative Example 2 (1) Dicalcium silicate powder was prepared by sol-gel method to obtain solid powder. The molar ratio of CaO:SiO2 was 2:1. The synthesis steps were the same as in Example 1.

[0051] (2) 0.5% (w / v) of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 10% (w / v) methacrylamide gelatin and 2.5% (w / v) oxidized gellan gum were added to water under light-protected conditions and dissolved completely to obtain a homogeneous liquid phase. The synthesis methods of gelma and oxidized gellan gum were the same as in Example 1.

[0052] (3) Mix 20wt% of solid powder with liquid phase to obtain injectable antioxidant silicon-calcium based material.

[0053] Comparative Example 3 (1) Magnesium-doped dicalcium silicate powder was prepared by sol-gel method to obtain solid powder. The molar ratio of CaO+MgO:SiO2 was 2:1. The synthesis steps were the same as in Example 1.

[0054] (2) 0.5% (w / v) of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 10% (w / v) methacrylamide gelatin and 2.5% (w / v) oxidized gellan gum were added to water under light-protected conditions and dissolved completely to obtain a homogeneous liquid phase. The synthesis methods of gelma and oxidized gellan gum were the same as in Example 1.

[0055] (3) Mix 20wt% of solid powder with liquid phase to obtain injectable antioxidant silicon-calcium based material.

[0056] Experimental testing and characterization The performance of each embodiment and comparative example is characterized below: 1. Determination of anti-collapse performance: The prepared paste was injected into a syringe into a glass dish containing deionized water. After standing for 10 minutes, photographs were taken to record the results and assess the anti-collapse ability of the un-illuminated sample. Another paste prepared using the same method was injected into a glass dish and irradiated for 30 seconds at a distance of 1.5 cm from the sample surface using a light-curing lamp with a wavelength of 405 nm and an intensity of 5 W. After standing for 18 hours, the degree of disintegration of the samples in water before and after irradiation was compared to comprehensively evaluate the effect of light irradiation on the anti-collapse performance of the paste.

[0057] Static anti-collapse performance tests were conducted using Examples 1-5 and Comparative Examples 1-3. Some results are as follows: Figure 1 , Figure 2As shown. Without UV irradiation, all groups of pastes collapsed after being injected with deionized water, exhibiting poor anti-collapse performance. After UV irradiation, the anti-collapse performance of all groups of pastes significantly improved. Among them, in Comparative Example 1, the solid powder mixed with deionized water did not exhibit good anti-collapse performance before and after photocuring. Examples 1-4 and Comparative Examples 2-3 only showed a small number of free particles after standing for 18 h. In Example 5, although the low content of methacrylamide gelatin led to a decrease in the density of the UV-induced photocrosslinking network, the increased content of oxidized gellan gum allowed its abundant aldehyde groups to form Schiff base chemical crosslinks with the amino groups in the paste, thereby constructing an additional stable crosslinking structure and compensating for the deficiency of photocrosslinking. Therefore, after UV irradiation, the paste of Example 5 could still maintain its initial shape, and although the number of free particles was relatively large, its anti-collapse performance was still significantly improved compared to the un-illuminated condition. The results indicate that methacrylamide gelatin and oxidized gellan gum synergistically improve the anti-collapse performance of the paste.

[0058] 2. Measurement of light curing time: Examples 1-5 and Comparative Examples 2-3 were tested under the same irradiation conditions as those used in the anti-collapse performance test. The results are as follows: Figure 3 As shown in the figures, in Examples 1-3 and Comparative Examples 2-3, the solid powder content was 20 wt%, and the photocuring time was approximately 11 s. In Example 4, the solid powder content was increased to 30%, and the curing time was extended to approximately 12 s. In Example 5, the solid powder content was 10%, and the curing time was shortened to approximately 9 s. This demonstrates a positive correlation between photocuring time and the solid powder content. Nevertheless, all groups were able to complete photocuring in a relatively short time, indicating that methacrylamide gelatin and oxidized gellan gum can work synergistically to significantly shorten the curing time of the paste, effectively overcoming the drawback of the long curing time of traditional calcium silicate-based pastes.

[0059] 3. Injection performance test: The prepared paste is filled into a 2.5 ml syringe and injected. The injection rate is determined by the ratio of the weight of the injected paste to the weight of the original paste.

[0060] The pastes from Examples 1-5 and Comparative Examples 2-3 were tested, and the results are as follows: Figure 4 As shown, the injection rate of all groups exceeded 90%, indicating that each paste group had good injectability. Furthermore, as... Figure 5 As shown, the pastes of Examples 2-4 can be injected continuously and smoothly during the extrusion process without any clogging.

[0061] 4. Reactive oxygen species scavenging test: The cured paste was ground into powder, and its overall antioxidant capacity and hydrogen peroxide scavenging ability were evaluated using the ABTS method and the titanium sulfate colorimetric method. The scavenging effect was determined by ultraviolet spectrophotometry (UV).

[0062] ABTS method: Mix the paste powder with ABTS + After the free radical solution was mixed and reacted for 30 min, the supernatant was collected by centrifugation, and its absorbance at a wavelength of 734 nm was measured using a UV-Vis spectrophotometer to evaluate the overall antioxidant capacity of the paste.

[0063] Titanium sulfate colorimetric method: The paste powder is mixed with 5 mM hydrogen peroxide solution and reacted. After centrifugation, the supernatant reacts with titanium sulfate reagent to generate a yellow peroxide-titanium complex. The absorbance curve is measured using a UV-Vis spectrophotometer to evaluate the scavenging ability of the paste for hydrogen peroxide.

[0064] Reactive oxygen species scavenging tests were conducted using Example 1 and Comparative Examples 2-3. Figure 6 and Figure 7 The results show that Example 1 exhibited the highest scavenging effect in both test methods, significantly outperforming Comparative Examples 2 and 3. The Ce ions doped in Example 1 possess unique Ce... 3+ / Ce 4+ The redox pair can mimic the activities of superoxide dismutase (SOD) and catalase, efficiently scavenging ABTS⁺ free radicals and hydrogen peroxide. Compared to Comparative Example 3, which only does not contain Mg ions, the introduction of Ce ions endows the paste with excellent free radical scavenging ability, thereby significantly improving the antioxidant properties of the material.

[0065] 5. Apatite mineralization performance test: The paste was cured in a 37°C water bath for 3 days to obtain solidified discs. These discs were then immersed in simulated body fluid (SBF) for 1 day, with the ratio of the immersed surface area to the SBF volume set to 0.1 cm². 2 / mL. After the soaking time is over, collect the sample, wash the sample surface with deionized water, and then dry it thoroughly in a 60 ℃ oven. Use SEM to observe the formation of apatite on the sample surface.

[0066] Tests were conducted using Comparative Example 2 and Example 1. The results are as follows: Figure 8 As shown, after soaking in SBF, a large amount of apatite can be deposited on the surface of the paste, indicating that the paste has excellent apatite deposition ability.

[0067] 6. Cell viability test Primary dental pulp stem cells (SHEDs) were cultured in α-MEM medium containing 10% fetal bovine serum and 1% penicillin / streptomycin, and maintained in a humidified incubator at 37 °C and 5% CO2. All experiments used SHEDs from passages 3-5. The solidified paste was ground into powder and added to the above medium, with a powder concentration of 5 mg / mL. The supernatant after centrifugation was collected to obtain the paste extract. Using SHEDs as experimental cells, cell viability of different bone cement materials was assessed using a CCK-8 cell technology kit. SHEDs were cultured in the paste extract, followed by the addition of CCK-8 reagent and incubation at 37 °C in the dark. Cell viability was then measured using a microplate reader.

[0068] Comparative Examples 2-3 and Example 1 were tested, and the cell viability after 1 day of culture was as follows: Figure 9 As shown, the cell activity of Comparative Example 3 and Example 1 was higher than that of Comparative Example 2, indicating that the doping of Mg ions can effectively improve the cell activity of the paste.

[0069] 7. ALP staining assay: SHED cells were cultured in α-MEM medium containing 10% fetal bovine serum and 1% penicillin / streptomycin, and maintained in a humidified incubator at 37°C and 5% CO2. All experiments used SHED cells from passages 3-5. Osteogenic conditioning medium was prepared by adding 50 μg / mL ascorbic acid, 10 mM β-glycerophosphate sodium, and 10 nM dexamethasone. The solidified paste was ground into powder and added to the above medium at a concentration of 5 mg / mL. The supernatant after centrifugation was collected to obtain bone cement extract. SHED cells were cultured in the bone cement extract for 14 days, then fixed with 4% formaldehyde and washed with PBS. The fixed cells were stained with ALP solution.

[0070] After performing ARS staining using Comparative Examples 2-3 and Example 1, the results are as follows: Figure 10 As shown, the color in Example 1 and Comparative Example 2 is significantly darker than that in Comparative Example 1, and the color in Example 1 is darker than that in Comparative Example 2. The doping of Mg ions and Ce ions can effectively enhance the alkaline phosphatase activity of the paste and endow the material with good early osteogenic induction ability.

[0071] 8. ARS staining assay: SHED cells were cultured in α-MEM medium containing 10% fetal bovine serum and 1% penicillin / streptomycin, and maintained in a humidified incubator at 37°C and 5% CO2. All experiments used SHED cells from passages 3-5. Osteogenic conditioning medium was prepared by adding 50 μg / mL ascorbic acid, 10 mM β-glycerophosphate sodium, and 10 nM dexamethasone. The solidified paste was ground into powder and added to the above medium at a concentration of 5 mg / mL. The supernatant after centrifugation was collected to obtain bone cement extract. SHED cells were cultured in the bone cement extract for 14 days, then fixed with 4% formaldehyde and washed with PBS. The fixed cells were stained with ARS solution.

[0072] After performing ARS staining using Comparative Examples 2-3 and Example 1, the results are as follows: Figure 11 As shown, the colors in Example 1 and Comparative Example 2 are significantly darker than those in Comparative Example 1. Meanwhile, the color of Example 1 is darker than that in Comparative Example 2, indicating that co-doping with Mg and Ce can promote the mineralization and deposition of the extracellular matrix more effectively than single doping, thereby significantly improving the osteogenic induction properties of the paste.

[0073] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0074] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.

Claims

1. An injectable antioxidant silica-calcium-based bioactive dental paste, characterized in that, It is made by mixing solid powder and liquid phase; The solid powder includes: magnesium-cerium co-doped dicalcium silicate powder; The liquid phase comprises an aqueous solution of lithium phenyl (2,4,6-trimethylbenzoyl)phosphate, methacrylamide gelatin, and oxidized gellan gum.

2. The injectable antioxidant silica-calcium-based bioactive dental paste according to claim 1, characterized in that, In the dental paste, the mass percentage of the solid powder is 10% to 30%.

3. The injectable antioxidant silica-calcium-based bioactive dental paste according to claim 1, characterized in that, In the magnesium-cerium co-doped dicalcium silicate powder, based on the total molar amount of the three metal elements calcium, magnesium, and cerium, the molar percentage of magnesium is 2.5% to 10%, and the molar percentage of cerium is 2.5% to 7.5%. Furthermore, the total molar amount of the three metallic elements calcium, magnesium, and cerium is in a molar ratio of 2:1 to that of silicon.

4. The injectable antioxidant silica-calcium-based bioactive dental paste according to claim 1, characterized in that, In the liquid phase, the mass-volume concentration of methacrylamide gelatin is 5 g / 100 mL to 15 g / 100 mL, and the mass-volume concentration of oxidized gellan gum is 1 g / 100 mL to 5 g / 100 mL.

5. The injectable antioxidant silica-calcium-based bioactive dental paste according to claim 4, characterized in that, The mass-volume concentration of lithium phenyl (2,4,6-trimethylbenzoyl)phosphate in the liquid phase is 0.5 g / 100 mL.

6. A method for preparing an injectable antioxidant silica-calcium-based bioactive dental paste according to any one of claims 1-5, characterized in that, Includes the following steps: Magnesium-cerium co-doped dicalcium silicate powder was prepared by sol-gel method and used as a solid-phase powder. Under light-protected conditions, methacrylamide gelatin, oxidized gellan gum, and lithium phenyl (2,4,6-trimethylbenzoyl)phosphate were dissolved in water to obtain a liquid phase. The solid powder and the liquid phase are uniformly mixed to obtain an injectable antioxidant silicon-calcium-based bioactive dental paste.

7. The method for preparing an injectable antioxidant silicon-calcium based bioactive dental paste according to claim 6, characterized in that, The magnesium-cerium co-doped dicalcium silicate powder is prepared by the sol-gel method, specifically including the following steps: The silicon source was added to ethanol and mixed and stirred. Then deionized water was added to obtain solution a. The pH value of solution a was adjusted to 1-2 with nitric acid and stirred until the silicon source was completely hydrolyzed to obtain solution b. Calcium source, magnesium source and cerium source are added to solution b, and the mixture is stirred continuously to obtain solution c. Solution c is cured until gelation occurs and then dried to obtain dry gel. The dry gel was ground into a fine powder, then calcined and cooled to room temperature, and then ground again to obtain the magnesium-cerium co-doped dicalcium silicate powder.

8. The method for preparing an injectable antioxidant calcium silicate-based bioactive dental paste according to claim 6, wherein the preparation process of the methacrylamide gelatin includes: Add gelatin to phosphate buffer and stir until completely dissolved to form solution d; Methacrylic anhydride was added to solution a and reacted under light-protected conditions; then it was diluted with phosphate buffer solution and the reaction was stirred. Finally, dialysis and freeze-drying were performed to obtain methacrylated gelatin.

9. The method for preparing an injectable antioxidant calcium silicate-based bioactive dental paste according to claim 6, wherein the preparation process of the oxidized gellan gum includes: Gellan gum is dissolved in deionized water to form solution e; Add sodium periodate to solution e and stir for 4 hours in the dark; Then add ethylene glycol and stir; Finally, after dialysis and freeze-drying, oxidized gellan gum was obtained.

10. The use of the injectable antioxidant silica-calcium-based bioactive dental paste according to any one of claims 1-5 in the preparation of dental filling and restorative materials, characterized in that, The dental filling and restorative material is used for root canal filling, apexification, or pulp capping.

Citation Information

Patent Citations

  • A calcium-silica-based composite bone cement with anti-collapse properties, its preparation method and application

    CN106693063B

  • Strontium-doped root canal filling paste as well as preparation method and application thereof

    CN118370689A